2020
DOI: 10.1111/ijcp.13748
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and COVID‐19: It is time to act

Abstract: Vitamin D (VitD) deficiency is considered a global problem and might be associated with increased susceptibility to COVID‐19 illness. In the light of COVID‐19 pandemic, VitD might be a promising agent for fighting the SARS‐CoV‐2, since VitD is involved in various pathophysiological mechanisms that occur during COVID‐19 infection. High‐dose VitD supplementation, particularly for risk groups, could be recommended to achieve and maintain optimal (range 40‐60 ng/mL) serum 25‐hydroxy vitamin D levels (marker of Vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 78 publications
(278 reference statements)
0
15
0
6
Order By: Relevance
“…However, a randomized controlled double-masked pilot study conducted in Spain has shown that the bolus dose is also effective in treating COVID-19 [ 28 ]. Though large-scale controlled study results have not yet been published, it appears better to recommend a high dose of vitamin D to the COVID-19 patients and people under quarantine as adjuvant therapy in support of other recommendations [ 127 ]. In such cases, calcifediol’s direct supplementation is highly recommended as it can quickly raise the serum vitamin D level [ 28 ].…”
Section: Acquiring Sufficient Levels Of Vitamin Dmentioning
confidence: 99%
“…However, a randomized controlled double-masked pilot study conducted in Spain has shown that the bolus dose is also effective in treating COVID-19 [ 28 ]. Though large-scale controlled study results have not yet been published, it appears better to recommend a high dose of vitamin D to the COVID-19 patients and people under quarantine as adjuvant therapy in support of other recommendations [ 127 ]. In such cases, calcifediol’s direct supplementation is highly recommended as it can quickly raise the serum vitamin D level [ 28 ].…”
Section: Acquiring Sufficient Levels Of Vitamin Dmentioning
confidence: 99%
“…Future studies focusing on embryonic and tissue-specific ace2 knockout and overexpression models can help understand the role of adaptive and innate immune system challenges in zebrafish liver expression variability. Moreover, a prognostic importance for Vitamin D has been shown in COVID-19 such that vitamin D exposure potentially increases ACE2 levels as well as reducing the risk for cytokine storm (Benskin, 2020;Bleizgys, 2020;Musavi et al, 2020). Herein we have identified a significant decrease in ace2 levels in response to Vitamin D treatment during early larval and organ .…”
Section: Discussionmentioning
confidence: 99%
“…11,12 To ensure prime treatment or even prevent COVID-19, several studies recommend maintaining 40-60nmol/L of vitamin D which can be achieved by giving dose of 1,000 IU/day. 13,14 For individuals deficient of vitamin D, up to 4,000 IU/day can be prescribed followed by 25(OH)D measurements following 1.5 months of intervention. 14…”
Section: Vitamin D Measurementmentioning
confidence: 99%
“…13,14 For individuals deficient of vitamin D, up to 4,000 IU/day can be prescribed followed by 25(OH)D measurements following 1.5 months of intervention. 14…”
Section: Vitamin D Measurementmentioning
confidence: 99%